Employability outcomes of human resource management and employment relations graduates. (3rd April 2022) - Ressia, Susan; Shaw, Amie
ABSTRACT: Knowledge, skills, abilities and attitudes (KSAAs) are important attributes required of university graduates to become effective Human Resource (HRM)/Employment Relations (ER) professionals. However, is what is taught and practiced at universities sufficient to equip graduates with the necessary KSAAs to meet employer expectations in industry? Furthermore, do graduates feel confident and job ready entering professional practice post completion of their undergraduate study? These questions raise important considerations around the effectiveness of the broader 'employability' agenda, and whether the immediate needs of both employers and graduates are being met. Insights into HRM/ER graduates' transition into employment were collected from 33 semi-structured interviews conducted with 15 HRM/ER graduates, 14 employers and four industry stakeholders within the field. The paper discusses graduates' transition from university to employment and whether they felt prepared in meeting employer expectations. Contrasting perspectives emerged as graduates indicated that they were satisfied with their university experience and subsequent transition to employment, while employers were mostly satisfied, they provided recommendations towards improving graduate outcomes. The research initiates new ideas for exploring the employability of university graduates and suggests further research in supporting the transition of future graduates into roles and careers in HRM and ER.